Reversal of Chemotherapy Resistance to Cisplatin in NSCLC by miRNA-195-5p via Targeting the FGF2 Gene - Wang H; Sui Z; Wu X; Tang P; Zhang H; Yu Z (Dove Medical Press, 2021)
Hao Wang,1,2 Zhi-lin Sui,1 Xian-xian Wu,1 Peng Tang,1 Hong-dian Zhang,1 Zhen-tao Yu1,3 1Department of Esophageal Cancer, Tianjin Medical University Cancer Institute and Hospital, Key Laboratory of Cancer Prevention and Therapy of Tianjin City, Tianjin, 300060, People’s Republic of China; 2Department of Surgical Oncology, Baotou Cancer Hospital, Baotou, People’s Republic of China; 3Department of Thoracic Surgery, National Cancer Center, National Clinical Research Center for Cancer, Cancer Hospital & Shenzhen Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Shenzhen, 518116, People’s Republic of ChinaCorrespondence: Zhen-tao Yu; Hong-dian ZhangDepartment of Esophageal Cancer, Tianjin Medical University Cancer Institute and Hospital, Key Laboratory of Cancer Prevention and Therapy of Tianjin City, Tianjin, 300060, People’s Republic of ChinaTel +86 22-23340123Fax +86 22-23359984Email yuzhentao@tjmuch.com; zhdiantjzl@tmu.edu.cnObjective: To explore the mechanism of miR-195-5p in the pathogenesis non-small cell lung cancer (NSCLC) and cisplatin resistance.Methods: The function of miR-195-5p in NSCLC and cisplatin resistance were determined by MTT, scratch assay, transwell assay, and nude mice xenograft experiments. miR-195-5p target gene was identified by dual-luciferase reporter assays and real-time PCR analysis.Results: miR-195-5p content was lower in A549/DDP than that in A549 cells, with reduced chemotherapy sensitivity and increased cell invasion and migration ability. The loss-of-function and gain-of-function assays illustrated that miR-195-5p might have increased the chemosensitivity to cisplatin in the A549/DDP cells and decreased cell migration and invasion. FGF2 is a negatively correlated action target of miR-195-5p. miR-195-5p might affect EMT by inhibiting FGF2. Overexpression of FGF2 resulted in enhanced cisplatin resistance in the cells, while miR-195-5p might have reversed this resistance.Conclusion: Overall, miR-195-5p might target FGF2 to reduce cisplatin resistance in A549/DDP cells and enhance chemosensitivity.Keywords: miR-195-5p, NSCLC, cisplatin, chemosensitivity, FGF2